6+9z=7

Simple and best practice solution for 6+9z=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+9z=7 equation:


Simplifying
6 + 9z = 7

Solving
6 + 9z = 7

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 9z = 7 + -6

Combine like terms: 6 + -6 = 0
0 + 9z = 7 + -6
9z = 7 + -6

Combine like terms: 7 + -6 = 1
9z = 1

Divide each side by '9'.
z = 0.1111111111

Simplifying
z = 0.1111111111

See similar equations:

| -6v+11=-4v+1 | | (-5i)+(I)= | | 2x^2+58=20x | | (-7)(8)-(-6)(-2)= | | 6x^2+2x-17=0 | | 1.5z=z | | 8x+10+2x=90 | | (1/x)+(1/x+3)=(1/4) | | -9z-9=-4z+6 | | 8+-25=-57 | | -6x-5=31 | | 18=2g+4 | | -8w-12=-2w+18 | | y/5-7=2 | | I-3=-7 | | x/(x+1)+(x+1)/x=3 | | 1=t/3-1 | | 2.7t+0.5=1.7t+6.5 | | (-5/4)(-9/8) | | -8u-18=15(u-1) | | 4-2c=2 | | 30=x-20 | | -5x-18=3(2x+5) | | 3w-5x-y+4w+20x-7y= | | 2.5=p+7.1 | | 8(x-9)=8(x+5) | | 2/7+5=-9 | | -4v=10 | | t+10/6=11 | | 16=7+3c | | c/2+11=15 | | -1.4v-0.8=4.3v-6.5 |

Equations solver categories